Influence of Seasonality on the Interaction of Mercury with Aquatic Humic Substances Extracted from the Middle Negro River Basin (Amazon) - de Oliveira, Luciana C.; Botero, Wander G.; Santos, Felipe A. [UNESP]; Sargentini, Ezio; Rocha, Julio C. [UNESP]; dos Santos, Ademir [UNESP] (Soc Brasileira Quimica, 2012)
High mercury concentrations in different environmental matrices in the Amazon have been attributed to mining activities. However, high concentrations of mercury are also present in the soil and water in places like in the middle of the Negro River Basin, which is far away from any anthropogenic emission sources. The Amazon region is characterized by two different regional seasons, with well-defined flood and low water periods. The objective of this work was to investigate the seasonal influences of the interaction between mercury and aquatic humic substances (AHS), which are the main agents of the natural organic complexation capacity. The results of the multivariate statistical analysis of the data showed that the humic substances had different structural characteristics, depending on each season. The ability of humic substances to form complexes with Hg(II) is not directly related to their carbon content, but to the nature and availability of the functional groups present in its structure. The functional groups are carboxylic and aromatic directly related to the higher complexation capacity of AHS by mercury ions.
Keywords: aquatic humic substances; seasonality; Negro River Basin; Amazonia; mercury